ANALISIS KELAYAKAN USAHA PEMBIBITAN PETERNAKAN KUDA PACU BUDI MULYA STABLE KOTA PAYAKUMBUH PROVINSI SUMATERA BARAT - Malik, Abdul; Priatna, Wahyu Budi (Forum Agribisnis, 2013)
Horses are animals that have many benefits for human life. One merits could get of a horse is sports riding. Horse race is one sports very most favorite by Indonesian people. One organization sports riding is PORDASI. Every year PORDASI make activities of a horse race high. Many projects of horse races are held PORDASI make the request a racehorse qualified to can fulfill a need the race. Budi Mulya Stable is a breeding horses race that have average sales horse six tail annually. In running their business, Budi Mulya Stable horses breeding had several obstacles. So required a feasibility analysis Â of business in order to see whether or not worthy of this business conduct. A feasibility analysis effort is done by analyzing at the non financial and financial aspects. Analysis aspect non financial consisting of market aspects, technical, management, law, socioeconomic environment. The aspect of financial analysis by means of analyzing criteria based on investment as NPV, Net B/ C, IRR, DPP and analysis Swiching Value.Â  The result of an feasibility analysis of this business that farm produce a racehorse budi mulya stable worthy to run.